Small albumin-immunoglobulin complexes in patients with liver disease. - Zhen, Q Y (1983)
Circulating immune complexes (CIC) with a molecular weight (M.W.) of 1.4-1.6 x 10(6) were observed in patients with liver disease. CIC containing abnormal albumin were found in patients with chronic active hepatitis. The abnormal albumin from CIC displayed an apparent M.W. of 105-110,000 on Sephadex G-100 and Sepharose 6B column chromatograph before reduction, and only 50,000 on reduced sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS-PAGE). It is postulated that abnormal albumin contained within CIC may be a dimeric-S-S-linked small albumin (sAlb-S-)2. Immunoglobulins in the CIC containing (sAlb-S-)2 were identified as IgM and IgG. Based on the constituents of CIC and their M.W., the assumed molecular formula of CIC is (IgM)1 (sAlb-S-)2 (IgG)3. Cause and effect of these CIC in liver disease, especially a possible role of altered host components in the initiation of autoimmune reactions, are discussed.